2005
DOI: 10.1158/0008-5472.can-05-1777
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the Genesis and Perpetuation of Cancer: Summary and Recommendations from a National Cancer Institute–Sponsored Meeting

Abstract: The Inflammation and Cancer Think Tank Meeting was organized by the National Cancer Institute with the purpose of identifying research advances, gaps, and opportunities for the study and clinical application of the role of inflammation on tumorigenesis. The format of this meeting consisted of brief presentations that focused on concepts, with extensive discussion periods to allow participants to identify issues and barriers limiting progress in this area. The strong relationship between inflammation and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 17 publications
0
51
0
Order By: Relevance
“…Using the mouse spontaneous mammary tumor model MMTV-PyT, we tested the ability of rapamycin to inhibit tumor growth at these doses. We initiated rapamycin treatment when the tumors first became palpable, at which point they had passed the angiogenic switch and were 50 to 100 mm 3 . We observed effective inhibition of tumor growth in control DTG mice at 0.1 and 0.5 mg/kg/d (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the mouse spontaneous mammary tumor model MMTV-PyT, we tested the ability of rapamycin to inhibit tumor growth at these doses. We initiated rapamycin treatment when the tumors first became palpable, at which point they had passed the angiogenic switch and were 50 to 100 mm 3 . We observed effective inhibition of tumor growth in control DTG mice at 0.1 and 0.5 mg/kg/d (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of the tumor microenvironment in regulating tumor growth and progression has been recently appreciated and targeted for therapy (1)(2)(3). Although there is evidence that the tumor stroma can acquire mutations and epigenetic alterations (4,5), it is still believed that most cells which are resident in the tumor microenvironment are more genetically stable than tumor cells and retain more normal responses to growth signals and other metabolic cues.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing recognition that inflammatory processes nurture developing malignancies in tissues before overt tumors are established (36). Local inflammation triggers the release of factors that can support the outgrowth of premalignant cells (37), whereas inflammation-associated immune activation may eliminate tumors or promote malignant progression by positively selecting for immune escape variants, a process collectively referred to as ''immunoediting'' (38).…”
Section: Discussionmentioning
confidence: 99%
“…For example Helibacter pylori infection and gastric cancer, inflammatory bowel disease and colon cancer, and hepatitis and hepatocellular carcinoma [28][29][30]. Subsequent studies that revealed an inverse relationship between long-term usage of anti-inflammatory medications and a decreased cancer risk support the support the direct association between chronic inflammation and cancer development [31]. Through a variety of cellular mediators, chemokines and cytokines, innate immune cells and T H 2 cells are able to create a pro-tumor microenvironment that favors cell proliferation, genomic instability and malignant conversion [32].…”
Section: Cancer Response To the Immune System: Exploitation And Evasimentioning
confidence: 99%